PERSEPSI DOSEN TETAP VOKASI UI TERHADAP PROSES BERBAGI PENGETAHUAN MELALUI COMMUNITIES OF PRACTICE (CoP) - Dyah Safitri (Jurnal Vokasi Indonesia, 2014)
ABSTRACTThe results of research on the perception of permanent lecturers vocational program UI for the sharing of knowledge through Communities of Practices (CoP). There are three research hypotheses were proved, namely (1) Perception of tenured faculty to sare knowledge is positive (2) The perception of permanent lecturers to positively CoP and (3) Perceptions of permanent lecturers of the document as a means of sharing knowledge through CoP. Results of the survey prove that the perception of permanent lecturers UI vocational program to three research hypothesis is positive. So that the CoP can be an alternative to teh creation of knowledge among tenured faculty vocational program UI. Limitations of the study is only for yhe organization and the results can be different if the study is an organization that has a different complexity.Keywords : Sharing knowledge, tenured faculty Vocational UI program, tacit knowledge, explicit knowledge